The deaf girl : a memoir of hearing loss, hope, and fighting against the odds - Heringer, Abigail (Sourcebooks, 2024)
"Abigail Heringer made her television debut as an instant fan-favorite on ABC's The Bachelor. Stepping out of the luxurious limo, she confidently approached her bachelor and let him know that she'd be staring at his lips all night for two reasons: (1) she was born deaf and (2) he has some nice-looking lips. But Abigail's life didn't start out with this level of self-assured energy. In fact, it started with barely any at all. As a deaf child and natural introvert, Abigail was terrified of the spotlight-always afraid of how people would react to her disability and how her presence would inconvenience others. But with the support of her family (especially her deaf older sister), she learned that the world would walk all over her if she let it. Only through becoming her fiercest advocate and loudest champion could she ever learn to find her own voice"--